Ethical Dilemmas in Public Policy The Dynamics of Social Values in the East-West Context of Hong Kong - Yung, Betty; Yu, Kam-por (Governance and Citizenship in Asia, 2016)
This book employs a unique interdisciplinary approach to analyze different ethical dilemmas in public policy, applying values and concepts to examine substantive policy and public issues that are grounded in practical realities (by integrating philosophy, political science, law, policy studies etc.), thereby bringing fresh insights to governance. Building on the nascent scholarly literature on the role of values in governance, it focuses on analyzing "social values in public policy" in the East-West context of Hong Kong, yielding new insights on how to achieve good governance by reflecting on public affairs and policy issues from a social values perspective. The book will be of interest to researchers, postgraduate and undergraduate students in the fields of philosophy, political science, public policy and social science in general, while politicians, public administrators, policy researchers and other professionals (e.g. teachers, journalists, social workers, doctors etc.) from both East and West will find it stimulating and constructive. The book offers well-founded reading and reference material for citizenship education, e.g. as teaching materials, especially for General Education courses at universities and Liberal Studies and Arts curricula in secondary schools. It also provides food for thought on the part of general citizens. "This will be a very important and unique book in the study of ethical pluralism and public policy in Hong Kong." - Professor Sonny Lo Shiu Hing "Public policy both reflects and shapes social values and social norms. However, the so- cial values and ethical dimensions of public policy are often left implicit and unexplored in policy analysis and policy formulation. The big questions - what kind of society do we want to create? What is at stake here? Whose values? - are debated and discussed in some other context which is more distant from the applied world of policymaking. This book takes a different position and puts ethical issues and social values up front in an exploration of a number of key public policy issues in Hong Kong. In doing so, the book makes a very timely intervention in Hong Kong's increasingly contentious public affairs and makes an important contribution to the general literature." - Professor Ray Forrest.